2006
DOI: 10.1016/j.virol.2006.07.008
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro analyses of a Bombyx mori nucleopolyhedrovirus mutant lacking functional vfgf

Abstract: All lepidopteran baculovirus genomes sequenced to date encode a viral fibroblast growth factor homolog (vfgf), suggesting that vfgf may play an important role in the infection cycle of lepidopteran baculoviruses. Here, we describe the characterization of a Bombyx mori nucleopolyhedrovirus (BmNPV) mutant lacking functional vfgf. We constructed a vfgf deletion mutant (BmFGFD) and characterized it in BmN cells and B. mori larvae. We observed that budded virus (BV) production was reduced in BmFGFD-infected BmN cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…Slower time of death implies that vfgf accelerates the rate of infection and insect death. Evidence for this is shown here and with another baculovirus (14).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Slower time of death implies that vfgf accelerates the rate of infection and insect death. Evidence for this is shown here and with another baculovirus (14).…”
Section: Discussionsupporting
confidence: 69%
“…Hosts infected with AcBAC-vfgfKO take longer to die, especially following oral infection (7,14). Slower time of death implies that vfgf accelerates the rate of infection and insect death.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that deletion of the egt gene from certain baculovirus genomes increases the speed of killing of the baculoviruses (O'Reilly & Miller, 1991;Flipsen et al, 1995;Chen et al, 2000). Fibroblast growth factor gene (fgf) is conserved in baculoviruses (Katsuma et al, 2004) and is involved in efficient BV production and stimulation of migration of insect cells (Katsuma et al, 2006;Detvisitsakun et al, 2007). The deletion of fgf delayed the time of death of infected larvae (Katsuma et al, 2006;Detvisitsakun et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast growth factor gene (fgf) is conserved in baculoviruses (Katsuma et al, 2004) and is involved in efficient BV production and stimulation of migration of insect cells (Katsuma et al, 2006;Detvisitsakun et al, 2007). The deletion of fgf delayed the time of death of infected larvae (Katsuma et al, 2006;Detvisitsakun et al, 2007). Baculovirus chitinase is involved in the liquefaction of infected larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Conserved only in alphabaculoviruses and betabaculoviruses, but absent in midgut-restricted gammabaculoviruses and deltabaculoviruses, viral FGF (vFGF) has been shown to accelerate BV exit from midgut cells and secondary infection by rerouting the host respiratory system to the midgut epithelium by mimicking host FGF. Although not essential for host infection per se, the difference in speed of establishment of systemic infection and speed of kill (Detvisitsakun et al, 2007;Katsuma et al, 2006) is thought to impact the capacity of any given virus to infect different hosts (Passarelli, 2011).…”
Section: Disease Progression In Alphabaculovirusesmentioning
confidence: 99%